ANALISIS PERTUMBUHAN EKONOMI, PENDIDIKAN DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KEMISKINAN DI MADURA - Nada Kirana Sari; Dwi Susilowati; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2020)
One of the main indicators of the success of a development is the reduction in poverty levels. Regency on Madura Island is the region with the highest poverty rate in East Java Province. The purpose of this study was to analyze the effect of economic growth, education and human development index on the poverty level of districts on the island of Madura 2012-2018. In this study using quantitative research and secondary data types sourced from the Central Statistics Agency. The regression analysis used is panel data with the chosen model that is Random Effect. The results of this study indicate that: 1). Partially economic growth, education and HDI have a negative and significant influence on the poverty level of districts on the island of Madura 2012-2018 2). Simultaneously economic growth, education and HDI have an influence on district poverty levels on the island of Madura 2012-2018. In this study concluded that the economic growth variable has a negative and significant effect on poverty levels with a probability value of 0,0001 and a coefficient of -0.180288. The education variable that uses the average length of school has a negative and significant effect on poverty levels with a probability value of 0.0000 and a coefficient of -2.174169. The human development index variable has a negative and significant effect on poverty levels with a probability value of 0,0001 and a coefficient of -0.540652.